Regulatory Focus, Boundaryless Mindset, and Creativity Among Chinese College Students: A Trait Activation Perspective - Luo, Nan; Xin, Xun; Li, Haihong; Yu, Xuan (Frontiers in Psychology, 2021)
We explored the impact of two types of regulatory focus on creativity among 330 college students in China, with the mediating role of boundaryless mindset and moderating role of stressful life events. A three-wave survey showed that both promotion focus and prevention focus positively predicted college students’ creativity, but the positive effect of promotion focus on college students’ creativity was more significant than that of prevention focus; boundaryless mindset mediated the relationship between regulatory focus and creativity; stressful life events moderated the direct effect promotion focus has on boundaryless mindset, and it also moderated the indirect effect promotion focus has on creativity via boundaryless mindset. These results extend existing research about creativity and establish a new mediating mechanism and boundary conditions between regulatory focus and college students’ creativity. Finally, we hope to provide a reference for innovation education.